Un Cynique à la cour : La collaboration de Giovan Marco di Parma avec l’atelier des Rapicano dans le scriptorium royal de Naples - Barreto, Joana (Pecia, 2018)
Abstract Giovan Marco di Parma, known as Cinico, occupies a special place in the Library of the Aragon in Naples in the 15th century. Scribe, he has ties of friendship with many humanists of the court, and even participates in the establishment of the printing press in Naples. His philosophical position, claiming Cynicism, earned him the admiration of his contemporaries and a great freedom in relation to administrative constraints. His philosophical commitment also pushes him to favor copies of history or political books. However, even if he is stoic, Giovan Marco fits perfectly into the courtesan life of his time. His collaboration with the great illuminateur Rapicano, shows thes ties between writing and painting in building an ideal portrait of the royalty. He even tries to soften the harshness of the king towards the barons by becoming author of miscellanea with partly controversial content.